Solar PV Construction Project Delays and Mitigation Strategies to Enhance Projects Timeline Performance A case study From Dubai’s Environment - AL-KHALIDI, ABDULRAHMAN BASIL (2022)
Distributed renewable generation projects are currently taking the major focus worldwide since it acts as the key enabler to the advanced grid structures such as smart grids and Virtual Power Plants (VPPs). The solar PV project construction forms the main driver for the international ambition toward reliable and sustainable energy transition. The United Arab Emirates led the renewable energy deployment in the region since 2014 till 2022 with more than 2.5 GW of installed capacity. Dubai distributed energy sector took the lead with almost 300MW of installed solar PV capacity by the end of 2021 with the ambition to cover 75% of the emirate’s energy mix by 2050. Such challenging targets will not be possible to materialize without optimizing project timeline management practices which will directly influence the deployment rates. The fundamental project issue of having construction delays applies to the solar PV industry and impacts the deployment rates, this topic needs to be evaluated carefully to limit the sequential effect on the project’s performance and the technology adaptability. This study looks to explore the actual delays in solar PV construction projects and consequently propose effective mitigation strategies to enhance the project’s timeline performance. This case study targets Dubai’s commercial solar PV industry using a quantitative data-collecting strategy and statistical analysis to draw the appropriate conclusion. In conclusion, all analyzed case studies in Dubai’s commercial-scale solar PV construction projects were confirmed to be delayed by 43% on average. The detailed root cause analysis on the abovementioned delay contribution in Dubai’s solar PV commercial scale projects resulted in four main delay categories starting with Site Condition Delays, Project Management Delays, Technical Design Delays and Logistical Delays. The study assessed the impact of each of these categories and proposed mitigation strategies to limit its occurrence in the future.